PENGARUH KEMAMPUAN KOMUNIKASI INTERPERSONAL, MOTIVASI BELAJAR DAN PEMANFAATAN PERPUSTAKAAN TERHADAP PRESTASI BELAJAR MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Ameta Cita Pinahasti; Armida Silvia (Jurnal Ecogen, 2018)
This research is based on one of the problems that always become the main topic in the field of education that is the problem of learning achievement along with the factors that influence it, with the consideration that the learning achievement is an indicator of the quality and quantity of knowledge controlled by the students. This study aims to determine the effect of several factors that allegedly affect learning achievement such as interpersonal communication skills, learning motivation and library utilization. The type of this research is descriptive and associative research. The population of this study is the year students entering 2013-2015 majoring in economics education Faculty of Economics State University of Padang registered in the academic year of July - December 2017 amounting to 256 people, the sample number of 72 people. The sampling technique is done by Proportional Random Sampling. Questionnaire is used as a data collection tool. Data analysis technique used is multiple linear regression. To test the hypothesis used F test and t test, using Statistical Product and Service Solution (SPSS) program. The results showed that there is a significant influence between interpersonal communication skills, learning motivation and library utilization together towards student achievement. Based on the results of the study suggested for students to further improve the ability of interpersonal communication, learning motivation and better utilization of the library in learning in order to get a more optimal achievement. For Lecturers expected to pay more attention to the condition of students in learning and for parents are expected to pay attention to the development of their children so as to provide encouragement to the students to remain eager in learning in order to get a better learning achievement This is evidenced by the results of research stating that the value of Fcount = 3.787 and sig value 0,014 < a = 0,05. Keyword: Interpersonal Communication Skills, Learning Motivation, library utilization and learning achievement.